The ethics of attaching research conditions to access to new health technologies. Issue 6 (16th February 2012) - Holland, Stephen; Hope, Tony
Abstract : Decisions on which new health technologies to provide are controversial because of the scarcity of healthcare resources, the competing demands of payers, providers and patients and the uncertainty of the evidence base. Given this, additional information about new health technologies is often considered valuable. One response is to make access to a new health technology conditional on further research. Access can be restricted to patients who participate in a research study, such as a randomised controlled trial; alternatively, a new treatment can be made generally available, but only on condition that further evidence is collected (eg, on long-term outcomes and adverse events, in patient registries). The National Institute for Health and Clinical Excellence (NICE), which provides guidance on which new health technologies to make available under the UK's NHS, for example, has made some research conditional recommendations, and the current interest in such options suggests that they are likely to become more prevalent in the future. This paper identifies and discusses the main ethical issues created by this distinctive range of recommendations. We argue that decisions to put research conditions on access to new technologies are compatible with widely accepted values, principles and practices relevant to resource allocation. However, there are important features of these distinctive judgements that must be taken into account by resource allocation decision-making bodies and research ethics committees, and that require new sorts of empirical data.